KEBIJAKAN PEMERINTAH KOTA DALAM MENGEMBANGKAN KOPERASI DI KOTA PEKANBARU TAHUN 2012 - Heryanto, Muhammad Adhe; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research has not been effected by the optimal policy in developing cooperatives by the Government of the city of Pekanbaru in 2012 and there is still a cooperative that is not active.Types and methods of research used descriptive research can be defined as the process of problem solving is investigated with a painted State of the subject and object of research in the current moment based on the facts that looked or how it is. Whereas the methods used are qualitative research methods to delineate the actual circumstances in detail and actual by looking at the problem and research objectives.In explaining the problems of research using model theory g. C Eduards III research analysis used as a guide. This research used the informant interviewees as object information that aims to reach ketuntasan in getting information in this study. Types and sources of data used in this research is the primary data and secondary data obtained through observation, documentation and interviews with the speakers.Based on the findings in the study that the Government policy of the city in developing the cooperative in the city of Pekanbaru in 2012 as stated in the Regulatory area of the city of Pekanbaru No. 08 in 2008 about the formation of the Organization, Position, and Duty Office-Office surroundings the City Government Soweto has very clear, but in fact in terms of developing cooperatives have not run optimally. This is due to the factors that influence the development of policies of this cooperative is a factor communication, resources, implementing the stance (dispositions), and bureaucratic structure.Keyword : Policy, The Development Of, Cooperative